Mathematics studies at the faculty of nature and mathematics of Vilnius university 1940–1944 - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2021)
Reorganization of the Polish Vilnius University of Steponas Batoras into Lithuanian Vilnius University in 1940 and the Faculty of Mathematics and Natural Sciences in 1940–1944.
Keywords: The Lithuanian Vilnius University; Faculty of Mathematics and Natural Sciences